Charmonium spectroscopy on dynamical anisotropic lattices - PEARDON, MICHAEL JAMES; RYAN, SINEAD MARIE; SKULLERUD, JONIVAR (Elsevier, 2006)
We present a first study of the charmonium spectrum on Nf = 2 dynamical, anisotropic lattices. We take advantage of all-to-all quark propagators to build spatially extended interpolating operators to increase the overlap with states not easily accessible with point propagators such as radially excited states of hc, y and cc, D-waves and hybrid states.
PUBLISHED
Keywords: Pure & Applied Mathematics